Toward epigenetic and gene regulation models of specific language impairment: looking for links among growth, genes, and impairments - Rice, Mabel L (BioMed Central, 2012)
Children with specific language impairment (SLI) are thought to have an inherited form of language impairment that spares other developmental domains. SLI shows strong heritability and recent linkage and association studies have replicated results for candidate genes. Regulatory regions of the genes may be involved. Behavioral growth models of language development of children with SLI reveal that the onset of language is delayed, and the growth trajectories of children with SLI parallel those of younger children without SLI. The rate of language acquisition decelerates in the pre-adolescent period, resulting in immature language levels for the children with SLI that persist into adolescence and beyond. Recent genetic and epigenetic discoveries and models relevant to language impairment are reviewed. T cell regulation of onset, acceleration, and deceleration signaling are described as potential conceptual parallels to the growth timing elements of language acquisition and impairment. A growth signaling disruption (GSD) hypothesis is proposed for SLI, which posits that faulty timing mechanisms at the cellular level, intrinsic to neurocortical functioning essential for language onset and growth regulation, are at the core of the growth outcomes of SLI. The GSD highlights the need to document and account for growth patterns over childhood and suggests needed directions for future investigation.